2015
DOI: 10.1002/pds.3924
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for confounding of interactions

Abstract: Studies of interactions should attempt to identify-as potential confounders-those risk factors whose associations with one of the exposures in the interaction term may be modified by the other exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Results did not differ (all-cause mortality rate ratio: 0.96 (0.89 to 1.04) vs 0.98 (0.91 to 1.07)). To ensure baseline differences in RA duration across the two cohorts did not confound the interaction,72 we adjusted the exponential PH models for RA duration at index date. To avoid near-collinearity between RA/control status and RA duration (which, by definition, equals 0 for all controls), RA duration in RA cases was centred to a mean of 0 73.…”
Section: Resultsmentioning
confidence: 99%
“…Results did not differ (all-cause mortality rate ratio: 0.96 (0.89 to 1.04) vs 0.98 (0.91 to 1.07)). To ensure baseline differences in RA duration across the two cohorts did not confound the interaction,72 we adjusted the exponential PH models for RA duration at index date. To avoid near-collinearity between RA/control status and RA duration (which, by definition, equals 0 for all controls), RA duration in RA cases was centred to a mean of 0 73.…”
Section: Resultsmentioning
confidence: 99%
“…Observational studies attempt to adjust for confounding of the treatment–outcome relationship but often do not consider any additional features required to unbiasedly evaluate TEM [ 5 ]. Here, we focus on the situation where the moderator not only influences the relationship between the treatment and outcome, but also the relationship between a confounder and either treatment receipt or the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This measure will help gauge how well outpatient care is coordinated with hospital care as this is an important aspect of care coordination that may help reduce hospital readmissions. 67 68 In addition, we will capture whether patients had a follow-up visit within 1 week post-discharge with any physician with whom they had had at least two visits in the 12 months preceding the index hospitalisation (community physician) or at least one visit during the hospital stay (hospital physician). 10 Research studies have reported that seeing a physician who is familiar with the patient’s health post-hospitalisation may have a beneficial impact on follow-up rates and reduce risk of death or re-admissions.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Bias in pharmacoepidemiology studies results from multiple sources of confounding. 67 71 72 DOAC users tend to be younger with fewer comorbidities than warfarin users. 73 To control for confounding, we will include variables such as age, sex, presence of specific comorbidities, concomitant medications, remote residence, neighbourhood income quintile and physician specialty among other independent variables in the model as potential risk factors.…”
Section: Methods and Analysismentioning
confidence: 99%